Pholiols E–K, lanostane-type triterpenes from Pholiota populnea with anti-inflammatory properties. (January 2023) - Yazdani, Morteza; Barta, Anita; Berkecz, Róbert; Agbadua, Orinamhe Godwin; Ványolós, Attila; Hohmann, Judit
Abstract: Investigation of the chloroform and ethyl acetate extracts of the edible mushroom Pholiota populnea led to the isolation of eight triterpenes, the undescribed natural products pholiols E–K and the known (+)-clavaric acid. HRESIMS and 1D and 2D NMR spectroscopy were employed to determine the structures of the undescribed compounds. The NOESY spectra were used to assign the relative configurations of triterpenes. The isolated compounds were screened for their anti-inflammatory activity on cyclooxygenase (COX-1 and COX-2), and lipoxygenase (5-LOX and 15-LOX) inhibitory assays. Dose–response investigations revealed that lanostane derivatives exhibited moderate 5-LOX and COX-2 inhibitory activities, with pholiol F (IC50 194.5 μM against 5-LOX and 439.8 μM against COX-2) the most active among the isolated compounds. Our findings indicated that P. populnea is an abundant source of new bioactive lanostane-type triterpenes. Graphical abstract: Image 1 Highlights: Lanostane triterpenes pholiols E-K were isolated from the CHCl3 and EtOAc fractions. The isolated compounds were investigated for anti-inflammatory activity. Pholiol F, and clavaric acid exhibited COX-2 inhibitory activity. Pholiols C, F, G, and I showed moderate 5-LOX inhibitory activity.